Botulinum toxin type A for treatment of hyperhidrosis. Issue 6 (November 2005) - Nelson, Lisa
Hyperhidrosis is defined as excessive sweating beyond that required to return the body temperature to normal. Focal hyperhidrosis commonly affects the axillae, palms, soles or face and often has a tremendous psychosocial and occupational impact on affected patients. To date, a variety of treatments have been used in the management of this condition, each with their own advantages and disadvantages. Botulinum toxin type A is licensed for the treatment of axillary hyperhidrosis but is now being used to treat several other types of focal hyperhidrosis. Botulinum toxins exert their effect by inhibiting the release of acetylcholine from autonomic cholinergic nerve terminals. Clinical trials investigating the use of botulinum toxin type A for axillary and palmar hyperhidrosis have shown a reduction in sweating and improvement in quality of life, with few reported side effects. This review discusses the use of botulinum toxin type A for the management of focal hyperhidrosis, relating to current evidence.